The Use of IT Tools In Event Management at The Crisis Level - Dariusz KLOSKOWSKI; Jerzy KORCZAK (Communications of International Proceedings, 2022)
The article is a proposal of using crisis response systems to manage events from the organizers' side. The presented characteristics of crisis management with the initiation of the SARS CoV-2 virus with reference to the meetings industry shows a niche interest in crisis IT systems from the event organizers, as evidenced by the cancellation of concerts, sports events, culinary festivals and the consequent collapse of the meetings industry. Reacting to the crisis was related to the received signals about the introduction of restrictions rather than reacting on the basis of developed procedures. The proposal to create a system with a specific IT tool presented in the work indicates the need for its implementation in the meetings industry, the breakdown of which significantly affects the mental state of society. In addition, bearing in mind the element of responding to similar situations, it turns out to be important to present a technical solution on the basis of which crisis events can be simulated. The proposed ICT solution: The Crisis Operational and Training Trainer is undoubtedly an innovative solution in which elements of event simulation are combined with operational activity. Crisis software implemented in the system is a proposal that results from current trends in presenting spatial data, with particular emphasis on cartographic solutions.
Keywords: crisis; event; crisis response system.